Penyakit Mosaik Pisang, Reaksi Inang, dan Pemurnian Virus - Sri Sulandari; Edy Purnawan (Jurnal Perlindungan Tanaman Indonesia, 1996)
Banana var. Koja showed mosaic symptoms sontained in Kotagede, Yogyakarta used in the studies. The virus then isolated with single lesion method on Chenopodium amaranticolor, and propagated on Nicotiana tabacum var. Xanthi. The result of host reaction study showed that infected Nicotiana tabacum var. Xanthi, N. tabacum var. Samsun, Cucumis sativus, and Lycopersicon esculentum produced systemic symptoms, while Chenopodium amaranticolor produced necrotic local lesions. Infected Vigna unguiculata did not produce any symptom. The purified virus obtained with the method of Scon showed A260/A280=1.21, with single protein m.w. 24.0 ×103. Virus showed serological relationship to CMV. All the result indicated that causal agent of banana mosaic disease has some similar properties with CMV.